2005
DOI: 10.1111/j.1540-8159.2005.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cost Savings by Telemedicine‐Assisted Long‐Term Care of Implantable Cardioverter Defibrillator Recipients

Abstract: Home monitoring (HM) of cardioverter defibrillators (ICD) with its automated wireless remote data access, may decrease the rate of patient visits. This study examined the potential cost savings for the long-term care of ICD assisted by HM. A French database including 502 patients from 6 university hospitals was used. Costs of conventional follow-up (FU) of ICD were calculated without, and compared with the expected cost of FU with HM. Calculations included number of visits, including physician's fees, electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 11 publications
1
71
0
9
Order By: Relevance
“…14,17 Our study design allowed total office evaluations to be reduced, although the proposed reduction in scheduled in-person encounters was less drastic than in other experiences. Indeed, in previous randomized trials, 18,19 regular 3-month visits were replaced with transmissions, and ICD patients underwent in-office evaluation every 12 or 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Our study design allowed total office evaluations to be reduced, although the proposed reduction in scheduled in-person encounters was less drastic than in other experiences. Indeed, in previous randomized trials, 18,19 regular 3-month visits were replaced with transmissions, and ICD patients underwent in-office evaluation every 12 or 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…Fauchier et al [12], in a retrospective analysis of 502 patients with remotely monitored ICDs, found that RM reduced the social costs of ICD follow-up by as much as USD 2,149 over the 5 years of expected life of the device. This study included the costs of transportation and medical services, but did not consider the cost of lost employment income for the time spent on in-hospital visits for patients and accompanying persons.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Most common reasons for unscheduled in-hospital or remote follow-ups were as follows: in the RM group, remote alerts for atrial or ventricular arrhythmia episodes [17], appropriate or inappropriate ICD therapy deliveries including anti-tachycardia pacing [12], out-of-range lead (pacing or shock) impedance [10], alerts for parameter values possibly related with a worsening heart failure [6], and other non-device-related causes [7]; in the control group, appropriate or inappropriate ICD shock deliveries [11], symptoms related with worsening heart failure [4] or atrial and ventricular arrhythmias not associated with ICD therapies [7], and other reasons [3]. All the unscheduled in-hospital visits in the RM group were triggered by RM alerts.…”
Section: Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma meta-análise baseada na avaliação de hospitalizações e custos numa população com insuficiência cardíaca desenvolvido na Alemanha, concluiu que os gastos hospitalares associados ao follow-up de doentes com dispositivos cardíacos se reduziam em cerca de 60% na modalidade de monitorização à distância 29 . Em termos de custos, a utilização da monitorização à distância tem a capacidade de reduzir os gastos totais do seguimento em doentes com dispositivos cardíacos implantados com benefício na relação custo-efetividade 11 .…”
Section: Custo-benefício Da Monitorização à Distânciaunclassified